REDOX REACTIONS IN HYDROCARBON CLASTIC RESERVOIRS: EXPERIMENTAL VALIDATION OF THIS MECHANISM FOR POROSITY ENHANCEMENT - Shebl M.A.; Surdam R.C. (My University, 1996)
Oil-rock-water reactions in hydrocarbon reservoirs were evaluated experimentally. Hematitic Tensleep Sandstone samples of 10-20 cm3 were heated with 200 ml of deionized water and 100 ml of petroleum for 3-14 days at 200-360oC. The Tensleep Sandstone samples are mature quartz arenites with 5-25% carbonate matrix and cement and minor amount of anhydrite pore-fillings.Results indicate that significant potential exists for redox reactions between oxidized mineral phases and crude oil. Iron oxides (+/- sulfate) were reduced and hydrocarbons were oxidized to oxygenated organic compounds (such as CO2 and organic acids). Organic acids generated during the redox reactions partitioned into the system water, dissolving framework grains and cements (primarily carbonates). Original porosity of the samples ranged from 6% to 15%, and increased by ~ 13-20%, to 7-18% or more after experimentation. As reactions between hydrocarbons and mineral oxidants proceed, redox reactions occur, under increasingly reducing condition as temperature increases, and result in enhanced sandstone reservoir porosity.